Jamming enabled variable stiffness wrist exoskeleton for tremor suppression - Wang, Guohui (2023)
Parkinson's disease is a chronic disorder that affects the central nervous system of patients. It affects millions of aging populations around the world every year. Approximately 80% of Parkinson's disease patients suffer from tremors which significantly reduce their life quality. In this study, we present a variable stiffness wrist exoskeleton (VSW-Exo) that is lightweight (less than 300 g on the wrist) and can effectively suppress wrist tremors in all three degrees of freedom. The functioning material of the variable stiffness unit is a novel chain mail-like structured fabric whose stiffness can be pneumatically controlled over a wide range under the jamming transition. Bending and Torsion tests are performed to characterize the VSW-Exo's damping force and torque. To evaluate the VSW-Exo's performance on human bodies, we devise vibration experiments to evaluate the prototype's performance on tremor suppression. The testing results show that our VSW-Exo's tremor suppression efficiency can reach up from 64.11 ± 10.92% to 67.24 ± 6.74%. Compared to other tremor suppression devices, our VSW-Exo can provide enough damping forces and torques to suppress tremors in all 3 directions with high efficiency and low weight on the wrist.